An econometric analysis of women's empowerment and fertility behavior in the Philippines - Espinosa, Caren Ianne dela Merced (School of Economics, University of the Philippines Diliman, 2018)
The Philippines witnessed a significant decline in total fertility rates over the last five decades. However, it continues to be the highest in the Southeast Asian region. In recent years, women_s empowerment has emerged as a prime focus for development efforts worldwide. With substantial evidence highlighting its effects on demographic outcomes, this paper underscores the importance of enhancing the social and economic footing of women in curbing fertility rates and in turn, fostering economic growth. The central assumption is that women with higher levels of empowerment prefer less children and use more contraception. Using data from the Philippine National Demographic Health (NDHS) 2013, it is found that this negative correlation holds in the local setting. Women who are employed and have access to resources use more contraceptives and desire a smaller family size. Higher levels of decision_making autonomy in the household also increase women_s ability to carry out their reproductive choices. Overall, it is illustrated that policies should be directed at improving women_s status and autonomy at the individual level, given substantial evidence that their roles in the private spheres of the household and relationships are more nuanced, and may have a stronger impact on their reproductive behavior.